Weed Study of Mulched Field in Mongolia - Sosorbaram, Saikhantsetseg; B., Baatartsol; J., Nambar; J., Otgon (International Journal For Research In Agricultural And Food Science, 2018)
As climate researchers predict, the surface air temperature increase rate in Mongolia is expected to be 3 times greater than the global average (0.770С), and may well exceed 2.00С, far greater than the maximum permissible rate. The surface temperature is estimated to rise at the rate of 2.7-3.60С in 2030-2040, and further 3.6-6.30С in 2080-2099, which can disrupt water cycle and precipitation patterns: mild increase in winter precipitation, as opposed to significant reduction in spring, summer and autumn precipitation, with estimated increase in evaporation by 7-10 times. Mongolia has an extreme continental climate, and its’ plant cover is loose, soil humus layer is thinner, has mainly light mechanically compounded soil, low precipitation in winter, dryness in spring. On the other hand, using a short rotation of grain fallow has created agro-ecological conditions such as vulnerable and a poorly-recovered environment. Under this situation, crop technologies need to be adapted to mitigate these negative consequences of the climate. Creating a large amount of plant covering will protect the soil from direct sunlight, and its consequences. The final result of our research work is focused on identifying the changes of soil moisture regime of the covered area furthermore, the positive and negative impacts on the soil, decrease of weeds. As a result of covering soil surface with straw, temperature reduced by 2 degrees during the planting season, weeds grew 3.4 times less, moisture of soil increased by 5.5 mm and plantlet of wheat seeds increased by 6.2 per cent respectively. As an average of study years weed quantity at mulched variants was less by 14 pc/m2 and less weight 7.1 g/m2 than mulch less variants, this was increased weight of main crop by 36.6 g/m2 and yield by 1.8 t/ha, respectively.